AMBITION OF FAUST IN JOHANN WOLFGANG VON GOETHE IN FAUST PLAY: A PSYCHOANALYTIC APPROACH - WARDANI, RINI KUSUMA (2010)
The research is proposed to analyze the ambition in a play with the title Faust with Psychoanalytic Approach. There are two objectives: the first is to analyze the play in term of structural elements, and the second is to analyze the play based on Psychoanalytic Approach. This study is a descriptive qualitative study, using the play of Goethe's Faust. And Faust the major character as the object of analysis of the study. There are two kinds of data sources used in this analysis, namely primary and secondary. The primary data are the play and script of the play itself and the secondary data sources are some books, internet and articles related to the subject. The technique of data collection in this research is library research by summarizing, paraphrasing and documenting the data. In analyzing the data, the researcher employs descriptive qualitative analysis. The analysis is started by analyzing the structural elements of the play. For the last, the researcher makes an analysis of Faust's id, ego, and superego. The researcher uses the theory of Psychoanalytic by Sigmund Freud because it is relevant to the problem. Based on the analysis, the outcome of this study shows that the problem of major character causes the ambition to get something is forbidden way. His way is unnatural and irrational; he cooperates with the devil but all of his properties have given to the human redemption, and finally he is saved by God in heaven.